Exosomal Long Non-Coding RNA ANCR Mediates Drug Resistance in Osteosarcoma - Hu, Xin; Wen, Yang; Tan, Lin-yun; Wang, Jie; Tang, Fan; Wang, Yi-tian; Zheng, Chuan-xi; Zhang, Yu-qi; Gong, Tao-jun; Min, Li (Frontiers in Oncology, 2022)
Osteosarcoma (OS) is rare cancer with bimodal age distribution with peaks observed in children and young adults. Typically, OS is treated with pre-surgery neoadjuvant therapy, surgical excision, and post-surgery chemotherapy. However, the efficacy of treatment on disease prognosis and objective response is not currently optimal, often resulting in drug resistance; in turn, highlighting the need to understand mechanisms driving resistance to therapy in OS patients. Using Doxycycline (Dox)-sensitive and resistant variants of OS cells lines KHOS and U2OS, we found that the resistant variants KHOS-DR and U2OS-DR have significantly higher in vitro proliferation. Treating the Dox-sensitive KHOS/U2OS cells with exosomes isolated from KHOS-DR/U2OS-DR made them resistant to treatment with Dox in vitro and in vivo and enhanced tumor growth and progression, while decreasing overall survival. Expression of the long non-coding RNA (lncRNA) ANCR was significantly higher in the KHOS-DR and U2OS-DR variants. SiRNA-mediated knockdown of ANCR decreased in vitro proliferation, while increasing sensitivity to Dox treatment in the KHOS-DR/U2OS-DR cells. Expression of the exosomal lncRNA ANCR was critical for drug resistance and OS tumor progression in xenografts and was correlated to resistance to Adriamycin and overall survival is patients with OS. These results establish lncRNA ANCR as a critical mediator of resistance to therapy in OS patients, highlighting it as a potential therapeutic target in OS patients.